2001
DOI: 10.1074/jbc.m102679200
|View full text |Cite
|
Sign up to set email alerts
|

The Nck-interacting Kinase (NIK) Phosphorylates the Na+-H+ Exchanger NHE1 and Regulates NHE1 Activation by Platelet-derived Growth Factor

Abstract: NIK, a recently identified Nck-interacting kinase, acts upstream of the MEK kinase MEKK1 to activate the c-Jun N-terminal kinase JNK. We now show that NIK binds to and divergently activates the plasma membrane Na ؉ -H ؉ exchanger NHE1. In a genetic screen, NHE1 interacted with NIK at a site N-terminal (amino acids 407-502) to the Nck-binding domain, and this site is critical for its association with NHE1 in vivo. NIK also phosphorylates NHE1; however, the phosphorylation sites, which are distal to amino acid 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
95
0
3

Year Published

2003
2003
2013
2013

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(101 citation statements)
references
References 49 publications
3
95
0
3
Order By: Relevance
“…2B). As a positive control we confirmed that NIK phosphorylated a GST fusion of the C terminus of the Na-H exchanger NHE1, as described (24) (Fig. 2B).…”
Section: Nik Activity Is Necessary For Lamellipodium Extension By Egfmentioning
confidence: 57%
See 3 more Smart Citations
“…2B). As a positive control we confirmed that NIK phosphorylated a GST fusion of the C terminus of the Na-H exchanger NHE1, as described (24) (Fig. 2B).…”
Section: Nik Activity Is Necessary For Lamellipodium Extension By Egfmentioning
confidence: 57%
“…Although STAT3 coprecipitates with HGK, its direct phosphorylation is undetermined. In mammalian fibroblasts NIK binds to the Na-H exchanger NHE1 and directly phosphorylates NHE1 to increase H ϩ efflux in response to PDGF (24). ERM proteins also bind to NHE1 (33), and by anchoring actin filaments ERM proteins maintain the localization of NHE1 at the leading edge of migrating fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regulation of NHE1 by these stimuli has been reported to occur through a variety of signaling molecules, i.e. calcinuerin B homologous protein (6,7), Ca 2ϩ /calmodulin (8,9), low molecular mass GTPases Ras and Rho (10 -12), p42/44 mitogen-activated protein kinases (13), p90 ribosomal S6 kinase (14), 14-3-3 protein (15), Nck-interacting kinase (16), and phosphatidylinositol 4,5-bisphosphate (17). However, the interrelationship of these signaling molecules and the mechanism by which they modulate the interaction of the putative H ϩ modifier site with intracellular protons is still unclear.…”
mentioning
confidence: 99%